The influence of Motivation on Work Efficiency of Public Organizations Employees in Chiang Mai Province - Prommayon, Preeda; Tharapitakwong, Suparerk; Kitthitinan, Phathranit; Sangkeaw, Sudarat; Panphare, Pichaphob (Research and Development Journal, Loei Rajabhat University, 2025)
This research was a quantitative study aimed at examining the motivation and work performance of Public Organizations Employees in Chiang Mai Province and testing the influence of motivation on the work performance of these employees. Data was collected through questionnaires from 251 of Public Organizations Employees in Chiang Mai Province. The data was analyzed using descriptive statistics to find percentages, means, and inferential statistics through factor analysis and multiple regression analysis. The research findings revealed that most employees were female, aged between 38-44 years, with a bachelor's degree. Their monthly income ranged between 15,001 – 20,000 baht, and their work experience ranged from 3 to 6 years. They were primarily employed in the Office of the Pinkanakorn Development Agency at the entry or general operational level. In terms of motivation affecting work performance, the study identified several key factors contributing to their job effectiveness, employees placed the highest importance on task achievement. There are three motivational factors that influence work performance: the ability to achieve results, career advancement, and recognition. These factors can predict work performance trends with 49.60%.